BOEREKRYGSGEVANGENES IN CEYLON - Henning, C.G. (Scientia Militaria - South African Journal of Military Studies, 2012)
"A PRISONER OF WAR HAS NO RIGHTS" "We can do what we like with a prisoner of war; we only have to keep him alive ... " (Engelse offisier aan Boere krygsgevangene)